Tailorable high-k and negative-k percolation behaviors in PPy/P(VDF-HFP) composites. (December 2021) - Xu, Wenfeng; Shi, Zhicheng; Sun, Shengbiao; Sun, Liang; Wang, Huanlei; Sun, Kai; Fan, Runhua
Abstract: Polymer-based composites with high permittivity and low loss are highly desirable for many applications such as embedded capacitors and pulse-power. In the meantime, percolating composites with negative permittivity can be promising candidates for metamaterials. In this paper, nanocomposites using conductive polypyrrole nanowires as fillers and poly(vinylidenefluoride-hexafluoropropylene) (P(VDF-HFP)) as matrix were prepared by a solution-casting method. The electrical properties were investigated in detail. Two types of percolation behavior were observed in the composites with increasing PPy content. The permittivity significantly enhanced when the PPy content exceeded high-dielectric percolation threshold (i.e. f high- k ) due to the large number of microcapacitors formed by PPy fillers and P(VDF-HFP) matrix. With further increasing PPy content, tunable negative permittivity behavior was achieved due to the formation of conductive networks, this phenomenon can be regarded as a negative-dielectric percolation (i.e. negative- k percolation), which can be well described by Drude-Lorentz model. The realization of high permittivity and tunable negative permittivity in PPy/P(VDF-HFP) nanocomposites gives a new and efficient strategy toward high- k materials and random metamaterials. Graphical abstract: Two types of percolation behaviors with different percolation thresholds, which bring about substantial changes of dielectric permittivity, are observed in PPy/P(VDF-HFP) composites. The relationship between the two percolation behaviors is clarified, which is of great significance for the rational design of high- k and negative- k composites. Image 1 Highlights: Two types of percolation behaviors with different percolation thresholds are observed in PPy/P(VDF-HFP) composites. The negative permittivity behavior is well described by Drude-Lorentz model. The relationship between the two percolation behaviors is clarified. The underlying conduction mechanisms corresponding to the two types of percolation behaviors are illuminated.